Clinical outcomes of integrated psychiatric and homoeopathic management in acute substance withdrawal: a case series - Sivakumar, Kothapalli; C., Rajikrishna R.; Mohan, N. D. (International Journal Of Community Medicine And Public Health, 2026)
Substance withdrawal is characterized by a cluster of symptoms and physiological changes that occur on reduction or cessation of prolonged or heavy substance use. The clinical features depend on the substance, dosage, and usage pattern, with alcohol, cannabis, and tobacco being among the most commonly implicated. Symptoms can range from mild discomfort to severe, life-threatening conditions. Standard management includes detoxification, medication-assisted therapy, and supportive care. Integrating psychiatry care with homoeopathy with may enhance outcomes by alleviating withdrawal symptoms, reducing stress, and supporting emotional balance, thereby improving recovery and reducing relapse risk. This case series aims to explore the Integration of standard care with homoeopathy to enhance treatment outcomes through individualized patient-centred intervention. Three young individuals with histories of alcohol, tobacco, and cannabis use presented to the psychiatry outpatient department of the national homoeopathy research institute, Kottayam, and were diagnosed with substance withdrawal as per ICD-10 criteria. Homoeopathic medicines, including Nux vomica and Staphysagria, were prescribed. In cases where the response was inadequate in some of the withdrawal symptoms, mild sedatives and antipsychotics (Lorazepam and olanzapine) were administered concurrently under psychiatric supervision and later tapered. This integrated approach resulted in noticeable relief from withdrawal symptoms within a few days and a sustained reduction in substance dependence over the following months. Treatment response, assessed using standard withdrawal scales for alcohol, cannabis, and tobacco, showed significant score reductions. While homoeopathy holds potential in managing acute substance withdrawal, the unpredictable nature of withdrawal progression makes Integration with psychiatric care a safer and more effective approach.